1978
DOI: 10.1152/jn.1978.41.6.1580
|View full text |Cite
|
Sign up to set email alerts
|

Controlled locomotion in the mesencephalic cat: distribution of facilitatory and inhibitory regions within pontine tegmentum

Abstract: 1. The contribution of postural tonus to controlled locomotion elicited by the stimulation of mesencephalic locomotor region (MLR) was studied in the acute precolicular-postmammillary decerebrate (mesencephalic) cat. 2. A microelectrode was placed in the unilateral MLR and another was placed systematically at 1-mm increments throughout the pons (H--4 to H--1O) at level ranging from P2 to P11 dorsoventrally and mediolaterally from 0 to L or R6. Depending on the general condition of the animal, stimuli through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 0 publications
2
53
0
Order By: Relevance
“…The locations of the cell bodies in the lower brain stem that are capable of initiating locomotion correspond to the MLR fiber terminations reported previously (Steeves and Jordan, 1984) and to the site where cooling to block synapse transmission reversibly abolished locomotion produced by electrical stimulation of the classical MLR (Shefchyk et al, 1984). The present study extends the MRF region previously shown to be capable of generating locomotion when electrically stimulated (Mori et al, 1978(Mori et al, , 1980Garcia-Rill and Skinner, 1987) and shows that an area from the midline to L2 can be stimulated electrically to induce locomotion. This confirms the previous finding by Mori et al (1978) that midline stimulation is effective for production of locomotion, but it is in contrast to the report by Garcia-Rill and Skinner (1987) who claim that midline stimulation does not produce locomotion.…”
Section: Mlr-reticulospinal Pathwaysupporting
confidence: 87%
See 4 more Smart Citations
“…The locations of the cell bodies in the lower brain stem that are capable of initiating locomotion correspond to the MLR fiber terminations reported previously (Steeves and Jordan, 1984) and to the site where cooling to block synapse transmission reversibly abolished locomotion produced by electrical stimulation of the classical MLR (Shefchyk et al, 1984). The present study extends the MRF region previously shown to be capable of generating locomotion when electrically stimulated (Mori et al, 1978(Mori et al, , 1980Garcia-Rill and Skinner, 1987) and shows that an area from the midline to L2 can be stimulated electrically to induce locomotion. This confirms the previous finding by Mori et al (1978) that midline stimulation is effective for production of locomotion, but it is in contrast to the report by Garcia-Rill and Skinner (1987) who claim that midline stimulation does not produce locomotion.…”
Section: Mlr-reticulospinal Pathwaysupporting
confidence: 87%
“…The present study extends the MRF region previously shown to be capable of generating locomotion when electrically stimulated (Mori et al, 1978(Mori et al, , 1980Garcia-Rill and Skinner, 1987) and shows that an area from the midline to L2 can be stimulated electrically to induce locomotion. This confirms the previous finding by Mori et al (1978) that midline stimulation is effective for production of locomotion, but it is in contrast to the report by Garcia-Rill and Skinner (1987) who claim that midline stimulation does not produce locomotion. The fact that the electrical threshold for the initiation of locomotion by stimulation of the MRF is higher than that observed for the MLR (Mori et al, 1980) or PLS (this study) suggests that a larger volume of tissue must be stimulated to produce locomotion, possibly due to a more diffuse distribution of neurons within the reticular formation.…”
Section: Mlr-reticulospinal Pathwaysupporting
confidence: 82%
See 3 more Smart Citations